Directors with foreign experience and corporate tax avoidance - Wen, Wen; Cui, Huijie; Ke, Yun (Journal of Corporate Finance, 2020)
Using a large sample of hand-collected directors' foreign experience data for Chinese listed companies from 2001 to 2016, we examine the impact of directors with foreign experience on corporate tax avoidance. We find a significantly negative association between directors with foreign experience and tax avoidance, suggesting that these directors can help constrain their firms' tax aggressiveness. The result is robust to Heckman two-stage analysis, instrumental variable approach, inclusion of potential omitted variables, change analysis, and alternative tax avoidance measures. Further analyses reveal that reputation concerns and CSR awareness are potential channels through which returnee directors affect corporate tax avoidance. The negative relation between directors with foreign experience and tax avoidance only holds when directors' foreign experiences are derived from countries or regions with higher investor protections. Non-independent directors with foreign experience have larger impacts on corporate tax avoidance than independent directors, and the effect is more pronounced when directors with foreign experience sit on audit committees. Directors' working and studying experiences both have important impacts on corporate tax avoidance. The result also suggests that the negative relation between directors with foreign experience and tax avoidance is more pronounced in non-state-owned firms. Overall, the findings suggest that directors' foreign experience matters for corporate tax behavior in emerging markets.